MOTIF CERAI GUGAT PADA PEREMPUAN DI DESA SUKOREJO KECAMATAN BOJONEGORO KABUPATEN BOJONEGORO - Vera Chontesa; Jatiningsih, Oksiana (Universitas Negeri Surabaya (Unesa), 2025)
This study aims to explore the motives behind divorce lawsuits filed by women in Sukorejo Village, Bojonegoro Sub-district, Bojonegoro Regency, and to determine whether gender understanding influences such actions. The research uses a qualitative approach with Alfred Schutz's phenomenological theory, which emphasizes understanding the subjective meaning of individual social actions. Data were collected through in-depth interviews with five female informants who had filed for divorce. The findings indicate that there are several motives behind women's decisions to divorce their husbands. The